Genetic characterization of Lactococcus garvieae isolated from farmed rainbow trout by random amplified polymorphic DNA-PCR in Iran - FADAEIFARD, F.; RABIEI, M.; SHARIFPOUR, M. F. (Journal of the Hellenic Veterinary Medical Society, 2020)
Lactococcosis is one of the main bacterial infections of fish around the world. Lactococcus garvieae has been a major cause of rainbow trout losses in freshwater farming. This study aimed to genotype and determine the variability of L. garvieae isolated from infected farmed rainbow trout in Iran by the RAPD-PCR method. Bacterial samples were collected from 12 farms located in the western part of Iran and suspect ted to carry Lactococcus infection. Two hundred bacterial cultures containing cocci shaped bacteria were cultured in Trypticase soy agar (TSA) and blood agar mediums. All bacterial cultures were tested by conventional microbiological and biochemical tests, and PCR assay to identify L. garvieae by 16S rDNA genes. The RAPD-PCR method was used to determine the genetic patternof all isolates. The sample strain pattern of the isolates was analyzed in the NTSYS program. According to a similarity coefficient index of 70%, all L. garvieae isolates were separated into two groups with four RAPD profile types. The highest and the lowest genetic pairwise similarity among the isolates were 98% and 54%, respectively. The results of the present study revealed that RAPD-PCR is an applicable method to describe the genetic diversity of different strains of L .garvieae among farmed fish.